2022
DOI: 10.3389/fcimb.2021.795026
|View full text |Cite
|
Sign up to set email alerts
|

A Model Predicting Mortality of Hospitalized Covid-19 Patients Four Days After Admission: Development, Internal and Temporal-External Validation

Abstract: ObjectiveTo develop and validate a prognostic model for in-hospital mortality after four days based on age, fever at admission and five haematological parameters routinely measured in hospitalized Covid-19 patients during the first four days after admission.MethodsHaematological parameters measured during the first 4 days after admission were subjected to a linear mixed model to obtain patient-specific intercepts and slopes for each parameter. A prediction model was built using logistic regression with variabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This might be a result from dependences and correlations that are specific for our set of predictors. Various prognostic models of mortality among patients with COVID-19 have been proposed [1] , [18] , [25] , [26] , [27] , [28] , [29] . Their predictive performance varied from fair (AUROC 0.7-0.8) to excellent (AUROC > 0.9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be a result from dependences and correlations that are specific for our set of predictors. Various prognostic models of mortality among patients with COVID-19 have been proposed [1] , [18] , [25] , [26] , [27] , [28] , [29] . Their predictive performance varied from fair (AUROC 0.7-0.8) to excellent (AUROC > 0.9).…”
Section: Discussionmentioning
confidence: 99%
“…Their predictive performance varied from fair (AUROC 0.7-0.8) to excellent (AUROC > 0.9). However, many studies showed high risk of bias [1] and only few temporally validate the models [27] , [28] , [29] . Our performance in the temporal validation is in line with another externally-validated model developed on EHR data [30] , as well as other studies that take into account readily availability data [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…This information was not considered in our analysis because it was incomplete and underreported, especially during the first phase of the pandemic. However, the literature has extensively demonstrated that patient age is the leading predictor of the most important outcomes of COVID-19 ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review released in July 2020 found many published prognostic scores estimating the mortality risk in COVID-19 patients, with a high or unclear risk of bias, of which the 4CM Score was considered promising [ 5 ]. Other scores were recently proposed [ 6 , 7 , 8 , 9 ]. The worldwide applicability of these predictive scores remains an open question because healthcare systems and patient profiles differ between countries, and may impact the scores’ performance [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%